A negociação de imagens identitárias na sentença judicial: o uso do conector embora como estratégia discursiva - Rafael Vinicius de Carvalho Picinin (2021)
In the ambit of a judicial proceeding, it is provided the litigant parties the right to diverge from one another. This divergence influences not only the behavior of the parties before Justice, but also the manner which the decisions will be built by the judge. Many times, objections are raised by the judge through concessive construction, in which is common the presence of the connector although in the court decision. In this master thesis, the discursive role of this connective in the judicial sentencing delivered by the judge Sérgio Moro in the case file no. 5046512-94.2016.4.04.7000/PR was researched. The general objective of this investigation is to understand through the connective although how identity images are built and negociated by the judge Sérgio Moro throughout the text in question. For this end, the Modular Approach to Discourse Analysis was adopted as instrument of analysis in view of its wide capacity to articulate information of linguistic, textual and situational orders. Based on the Modular Approach, the relational organisation of the judgement is studied focusing on the segments in which the connective although is used. Furthermore, for the study of syntactics, semantics and pragmatics properties of the connective, contributions from the Traditional Grammar, Semantics of Enunciation and from Functionalism have been taken into account. Throughout this thesis, the judicial sentencing has been described and presented. Such genre is characterized by revealing the announcement through which the judge puts an end to a cognizance proceedings or execution proceedings. Moreover, lexical, syntactic, semantic and pragmatic properties of the connective have been identified. Following that, the hierarchy of the textual constituents were presented, to thereby describe, analise and interpret the purpose of such concessive enunciation. In this analysis, the 30 occurences produced by the judge have been analysed from generic relations point of view and, thereafter, from specific relations point of view which they signal. The generic analysis stated that although performs as a marker of counter-argument. Whereas, the specific analysis revealed a relation of objection, refutation of opposing arguments. In conclusion, the balance of results suggests that the judge, in general, is not able to, through the connective although, stablish clear enough and justified propositions from the discursive point of view. This because, by fomulating his enunciations, the judge faces opposing allegations as if such were personal offenses, without promoting, however, depth in legal debate. With such, the process of negotiation of identity images, signaled by this connective in the sentence, is harmed, thus, making impossible the construction of a positive image of the judge.